CAMPUR KODE DALAM NOVEL SABTU BERSAMA BAPAK KARYA ADHITYA MULYA - Septiani, Rizki; Saman, Sisilya; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe selection of the novel Sabtu Bersama Bapak by Adhitya Mulya as an object of research based on several reasons. First, code mixing was not only in oral form, but also in writing. Second, based on the findings of researchers that in the novel there are many elements of foreign languages found. Third, the writer of the novel can be said to be a literary class of 2000s. This research was conducted to describe the form of code mixing, code mixing function, and exposure to the contribution of research results to learning. The research method used is descriptive research method with qualitative forms. The data of this study were in the form of dialogue between the characters of the novel. Data analysis techniques in this study were qualitative data analysis. In the novel there is a mixture of tangible words, phrases, clauses, baster, rephrase, and expressions / idioms. The code mix contained in the novel serves as the insertion of sentences and as a specification of the opponent's speech. The results of the study were contributed to Indonesian language learning in the second semester of the 11th grade on basic competencies 3.17.Â Keywords: Code Mixing, Form Of Code Mixing, Code Mixing Function, Novel